Accelerating Onset of Puberty Through Modification of Early Life Nutrition Induces Modest but Persistent Changes in Bull Sperm DNA Methylation Profiles Post-puberty - Jean-Philippe Perrier; David A. Kenny; Aurélie Chaulot-Talmon; Aurélie Chaulot-Talmon; Colin J. Byrne; Colin J. Byrne; Eli Sellem; Luc Jouneau; Luc Jouneau; Anne Aubert-Frambourg; Anne Aubert-Frambourg; Laurent Schibler; et al. (Frontiers in Genetics, 2020)
In humans and model species, alterations of sperm DNA methylation patterns have been reported in cases of spermatogenesis defects, male infertility and exposure to toxins or nutritional challenges, suggesting that a memory of environmental or physiological changes is recorded in the sperm methylome. The objective of this study was to ascertain if early life plane of nutrition could have a latent effect on DNA methylation patterns in sperm produced post-puberty. Holstein-Friesian calves were assigned to either a high (H) or moderate (M) plane of nutrition for the first 24 weeks of age, then reassigned to the M diet until puberty, resulting in HM and MM groups. Sperm DNA methylation patterns from contrasted subgroups of bulls in the HM (ejaculates recovered at 15 months of age; n = 9) and in the MM (15 and 16 months of age; n = 7 and 9, respectively) were obtained using Reduced Representation Bisulfite Sequencing. Both 15 and 16 months were selected in the MM treatment as these bulls reached puberty approximately 1 month after the HM bulls. Hierarchical clustering demonstrated that inter-individual variability unrelated to diet or age dominated DNA methylation profiles. While the comparison between 15 and 16 months of age revealed almost no change, 580 differentially methylated CpGs (DMCs) were identified between the HM and MM groups. Differentially methylated CpGs were mostly hypermethylated in the HM group, and enriched in endogenous retrotransposons, introns, intergenic regions, and shores and shelves of CpG islands. Furthermore, genes involved in spermatogenesis, Sertoli cell function, and the hypothalamic–pituitary–gonadal axis were targeted by differential methylation when HM and MM groups were compared at 15 months of age, reflecting the earlier timing of puberty onset in the HM bulls. In contrast, the genes still differentially methylated in MM bulls at 16 months of age were enriched for ATP-binding molecular function, suggesting that changes to the sperm methylome could persist even after the HM and MM bulls reached a similar level of sexual maturity. Together, results demonstrate that enhanced plane of nutrition in pre-pubertal calves associated with advanced puberty induced modest but persistent changes in sperm DNA methylation profiles after puberty.